2021
DOI: 10.7570/jomes20100
|View full text |Cite
|
Sign up to set email alerts
|

Does Obesity Affect the Severity of Exercise-Induced Muscle Injury?

Abstract: This is a PDF file of an article accepted, but it is not yet the definitive version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
(94 reference statements)
0
11
0
1
Order By: Relevance
“…In fact, obese subjects have higher level of leptin, a pro-inflammatory adipokine, and lower level of adiponectin, an anti-inflammatory adipokine. 5 , 6 Kim and Yoon 1 reported that excess body fat is associated with increased levels of inflammatory markers such as interleukin-7 and C-reactive protein in postmenopausal women and in elderly obese women, supporting the relationship between obesity and inflammation. The researchers also underline that obesity-induced inflammatory responses are highly likely to contribute to the increase in post-exercise delayed onset muscle soreness (DOMS) severity.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…In fact, obese subjects have higher level of leptin, a pro-inflammatory adipokine, and lower level of adiponectin, an anti-inflammatory adipokine. 5 , 6 Kim and Yoon 1 reported that excess body fat is associated with increased levels of inflammatory markers such as interleukin-7 and C-reactive protein in postmenopausal women and in elderly obese women, supporting the relationship between obesity and inflammation. The researchers also underline that obesity-induced inflammatory responses are highly likely to contribute to the increase in post-exercise delayed onset muscle soreness (DOMS) severity.…”
mentioning
confidence: 91%
“…1 Although the causes of DOMS are unclear, a major hypothesis suggests inflammatory responses as one cause. 1 Obesity is an important cardiovascular risk factor in women, especially visceral obesity that develops during menopause and is associated with high levels of inflammation. 2,7 Furthermore, obesity is associated with other co-morbidities that are no less dangerous than obesity itself, such as essential hypertension, atherosclerosis, coronary artery diseases, type 2 diabetes mellitus, and cerebrovascular stroke.…”
mentioning
confidence: 99%
See 3 more Smart Citations